The Relationships Between the Level of Knowledge and the Incidence of Anemia in Adolescent Girl - Ika Mustika Dewi; Prastiwi Putri Basuki; Ratri Candra Marlina (LPPM STIKES KENDAL, 2020)
Anemia is one of the common nutritional disorders and a major nutritional problem in Indonesia. Adolescent girl are one group that has a high prevalence of anemia. This because at puberty, they lose a lot of iron during menstruation and are exacerbated by a lack of iron intake so that they have ten times greater risk of anemia. The research objective is to determine the relationship between the level of knowledge and the incidence of anemia in adolescent girl. This research is a Non-Experimental study with a correlational research design use a cross sectional approach. The population in this study were X grade students of the 2019/2020 school year at SMKN Tepus, Gunung Kidul, DIY. The sampling technique is a total sampling with a total of 77 people. Data collection was performed was carried out using a questionnaire and checking the hemoglobin level in the blood using a hemocue device. The knowledge questionnaire was tested for validity using Pearson product moment. The data obtained were valid whit r count > r table (0.444). Reliability test using Cronbach alpha showed reliable results with a value of α = 0.854 > 0.6. Based on the Chi Square test, the p value = 0.024 (p value < 0.05) was obtained, so Hα was accepted and Ho was rejected. There is a relationship between the level of knowledge and the incidence of anemia in adolescent girls in class X at SMK N Tepus Gunungkidul.